(untitled) (Scientia Agricola, 2013)
Replacing conventional tillage (CT) with no-tillage (NT) management alters the pedoenvironment and the rate of topsoil processes, with possible effects on dissolution processes associated with iron oxides and therefore soil mineralogy. This study aimed to determine the effect of NT on the content and distribution of types of iron oxides in a Rhodic Paleudult in southern Brazil. Soil samples were collected at eight depths within the 0.00-0.80 m layer under CT and NT in a long-term experiment (21 years). Mineralogical identification was conducted by X-ray diffraction (XRD), and the Fe content related to specific types of iron oxides determined by selective dissolution and diffuse-reflectance spectroscopy. Kaolinite, quartz, goethite, hematite, and maghemite were identified in the clay fraction. In the NT-managed soil, there was a decrease in the content of crystalline iron oxides and an increase in the content of poorly crystalline iron oxides with increasing proximity to the soil surface. These results suggest that iron oxides are rearranged in this soil by reductive dissolution of the crystalline types and neoformation of metastable ferrihydrite in topsoil layers, which should be assessed further in laboratory studies.